Enhancing FSKTM Pre-Viva Management Through Online System - Derrick Tee Yee Meng; Mahdin, Hairulnizam (Applied Information Technology And Computer Science, 2024)
The pre-viva management system is a system that enables the postgraduate student to apply for pre-viva and for admin to manage pre-viva. The current pre-viva system in FSKTM is using internet tools and hand-writing of the application.  This make the pre-viva application become no efficiency. Therefore, a web-based pre-viva management system will be proposed and developed to improve the process. The system development followed the waterfall methodology. The system will be implemented using XAMPP, PHP,  Visual Studio Code, and 000webhost. At the end of the project, a fully functional web-based online system will be developed. Now the web-based system had been develop completely with user-friendly interface